2014
DOI: 10.3758/s13423-014-0686-2
|View full text |Cite
|
Sign up to set email alerts
|

The effects of increasing target prevalence on information processing during visual search

Abstract: The proportion of trials on which a target is presented (referred to as the target prevalence) during visual search influences the probability that the target will be detected. As prevalence increases, participants become biased toward reporting that the target is present. This bias results in an increase in detection rates for the target, coupled with an increased likelihood of making a false alarm. Previous work has demonstrated that, as prevalence increases, participants spend an increasing period of time s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
53
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(65 citation statements)
references
References 18 publications
11
53
1
Order By: Relevance
“…Eye-tracking analyses showed that common targets were found more efficiently and identified more quickly than rare targets. Our findings strongly align with recent work by Godwin and colleagues (Godwin, Menneer, Cave, et al, 2015; Godwin, Menneer, Riggs, et al, 2015) and extend their work in two important ways. First, our RSVP experiments (Experiments 3 and 4) demonstrate that LPEs arise even when early search termination errors are not possible and when reflexive motor errors are extremely unlikely.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Eye-tracking analyses showed that common targets were found more efficiently and identified more quickly than rare targets. Our findings strongly align with recent work by Godwin and colleagues (Godwin, Menneer, Cave, et al, 2015; Godwin, Menneer, Riggs, et al, 2015) and extend their work in two important ways. First, our RSVP experiments (Experiments 3 and 4) demonstrate that LPEs arise even when early search termination errors are not possible and when reflexive motor errors are extremely unlikely.…”
Section: Resultssupporting
confidence: 93%
“…Once an observer has learned not to expect certain targets, it becomes more difficult for those targets to attract attention and more difficult for them to resonate with search intentions held in memory. Indeed, our findings are also in alignment with a more recent investigation by Godwin and colleagues (Godwin, Menneer, Riggs, et al, 2015; see also Godwin, Menneer, Cave, et al, 2015); their participants searched for two rotated T s (that differed considerably in color) among rotated L s (of assorted colors). As in our experiments, one target color was present in 45% of trials and its counterpart in 5% of trials.…”
Section: Discussionsupporting
confidence: 92%
“…This is very similar to the pattern of effects observed for the inexperienced participants, who spent longer searching and were more likely to respond 'haltpatrol' than the experienced participants. But the similarities go deeper still: in a previous study (Godwin et al, 2014), we also found that, when participants expected a target to be present, they made repeated visits to objects, just as the inexperienced participants did here with the PRIs.…”
Section: Discussionsupporting
confidence: 57%
“…However, in X-ray baggage screeners, there is a cost associated with this increase in accuracy: search is more accurate but less rapid for experienced searchers, who approach search in a consistently more cautious manner. This finding suggests that experienced X-ray baggage screeners may be more exhaustive in their searchers (Wolfe, Brunelli, Rubinstein, & Horowitz, 2013), perhaps due to spending longer examining each object or examining more objects (Godwin, Menneer, Cave, Thaibsyah, & Donnelly, 2014).…”
mentioning
confidence: 96%
“…The visual search tasks that are often used in the literature are, however, typically context-free searches for arbitrary features, such as black vertical and horizontal lines on a white background (Wolfe & Friedman-Hill, 1992). Even when experimenters use naturalistic stimuli, these are typically impoverished in order to maintain a high degree of experimental control (Godwin, Menneer, Cave, Thaibsyah, & Donnelly, 2015). This is further complicated by the dynamic stimuli used in this current study.…”
Section: Discussionmentioning
confidence: 99%